2016
DOI: 10.1186/s12967-016-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of upstream TH2-cytokines in a mouse model of viral-induced asthma exacerbation

Abstract: BackgroundExacerbations of asthma caused by respiratory viral infections are serious conditions in need of novel treatment. To this end animal models of asthma exacerbations are warranted. We have shown that dsRNA challenges or rhinoviral infection produce exacerbation effects in mice with ovalbumin (OVA)-induced allergic asthma. However, house dust mite (HDM) is a more human asthma-relevant allergen than OVA. We thus hypothesised that dsRNA challenges in mice with HDM-induced experimental asthma would produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…Consistent with increased expression of TSLP, HDM stress could induce NF‐κB expression in airway epithelial cells from ITGB4 +/+ mice. These results were consistent with previous studies from different cells and animal models . In addition, a significantly increased expression of NF‐κB was detected in HDM stressed ITGB4 −/− mice group compared with HDM stressed ITGB4 +/+ group (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with increased expression of TSLP, HDM stress could induce NF‐κB expression in airway epithelial cells from ITGB4 +/+ mice. These results were consistent with previous studies from different cells and animal models . In addition, a significantly increased expression of NF‐κB was detected in HDM stressed ITGB4 −/− mice group compared with HDM stressed ITGB4 +/+ group (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These results were consistent with previous studies from different cells and animal models. 42,43 In addition, a significantly increased expression of NF-B was detected in HDM stressed ITGB4 −/− mice group compared with HDM stressed ITGB4 +/+ group (Fig. 5B).…”
Section: Increased Expression Of Tslp Was Induced By Activation Of Nfmentioning
confidence: 85%
“…A meta‐phenome‐wide association study also revealed a novel association of an IFIH1 allele mutation to increased risk for asthma . In an experimental model, poly(I:C) and rhinovirus‐derived dsRNA exacerbated asthma . Taken together, RLRs play a nonredundant and critical role in the development and progression of asthma.…”
Section: Rig‐i‐like Receptorsmentioning
confidence: 93%
“…Experiments were approved by the regional laboratory animal ethics committee in Malmö/Lund (permit no. M36-13) and performed as previously described [ 10 ]. In short, C57BL/6 wild-type and caspase-1 -/- mice (provided by Catharina Svanborg, Lund University, Lund, Sweden) were challenged with 25 µg house dust mite (HDM; Greer, Lenoir, NC, USA) 3 days·week −1 for 3 weeks and were subsequently exposed to three doses of 50 µg polyinosinic:polycytidylic acid (poly(I:C); InvivoGen, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%